Quantification of Correlation Between Geometric Characteristics for The Hexagonal Discrete Global Grid Systems - Luo, Fuli; Lu, Qiang; Wang, Zheng (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2024)
Although the discrete global grid systems can serve as a robust digital Earth framework, the geometric complexity of grid cells increase with the level of divisions due to the inherent topology of the spherical surface. Research on the correlation of geometric characteristics is essential for describing these complexities. Recently, researches have paid more attention to global triangular and diamond grid systems, but have not yet investigated the correlation relationships among multiple geometric features of global hexagonal grid systems. This constrains significantly the application expansion in high-precision spatial data processing and analysis, Earth system modeling, and complex phenomena simulation. In this study, we selected seven indicators from the Goodchild Criteria to quantify the geometric features, calculated and identified features' correlations at various resolutions, and constructed a correlation model of multiple quantitative indicators. Results with the ISEA4H grid model as the subject indicate a strong correlation among intrinsic geometric features, while topological features exhibit notably high independence. Our study reveals the correlation among multiple geometric features of hexagonal discrete global grid systems, laying a foundation for their comprehensive quality evaluation system.